THE INORGANIC PHOSPHATE CONTENTS IN THE MUSCLES OF SOME TELEOSTS OF DIFFERENT FEEDING HABITS IN THE RED SEA (Biological Sciences - PJSIR, 2002)
The inorganic phosphate (Pi) contents of the muscles of some economically important  Red  Sea teleosts were  determined.  The fish species included were of different feeding habits: carnivorous, omnivorous and herbivorous.  Herbivore  group  showed the highest level of inorganic phosphate followed by omnivore and carnivore. The variations of the total content of inorganic  phosphate  existed  in the muscle  of fish of the same feeding habit do   exist.